2012
DOI: 10.1007/s00213-012-2809-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent effects of chronic clozapine on the cellular and behavioral responses to LSD in mice

Abstract: Rationale In schizophrenia patients, optimal treatment with antipsychotics requires weeks to months of sustained drug therapy. However, single administration of antipsychotic drugs can reverse schizophrenia-like behavioral alterations in rodent models of psychosis. This raises questions about the physiological relevance of such antipsychotic-like activity. Objective This study evaluates the effects of chronic treatment with clozapine on the cellular and behavioral responses induced by the hallucinogenic sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 56 publications
(83 reference statements)
1
15
0
Order By: Relevance
“…Another approach to determine the therapeutic-like effects of chronic treatment with antipsychotic drugs is based on the use of LSD as a mouse model of psychosis (Gonzalez-Maeso et al, 2008; Kurita et al, 2012; Moreno et al, 2013a, b). Administration of psychedelic 5-HT 2A receptor agonists induces expression of the immediate early genes c-fos, egr-1 and egr-2 in mouse somatosensory cortex (Gonzalez-Maeso et al, 2003,2007; Moreno et al, 2013a, b).…”
Section: Behaviour Models Of Chronic Antipsychotic Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach to determine the therapeutic-like effects of chronic treatment with antipsychotic drugs is based on the use of LSD as a mouse model of psychosis (Gonzalez-Maeso et al, 2008; Kurita et al, 2012; Moreno et al, 2013a, b). Administration of psychedelic 5-HT 2A receptor agonists induces expression of the immediate early genes c-fos, egr-1 and egr-2 in mouse somatosensory cortex (Gonzalez-Maeso et al, 2003,2007; Moreno et al, 2013a, b).…”
Section: Behaviour Models Of Chronic Antipsychotic Treatmentmentioning
confidence: 99%
“…Administration of psychedelic 5-HT 2A receptor agonists induces expression of the immediate early genes c-fos, egr-1 and egr-2 in mouse somatosensory cortex (Gonzalez-Maeso et al, 2003,2007; Moreno et al, 2013a, b). The authors found that chronic (21 d), but not sub-chronic (2 d), treatment with clozapine eliminates the induction of c-fos, egr-1 and egr-2 by LSD 1 d after the final injection (Moreno et al, 2013b). The induction of c-fos, egr-1 and egr-2 by LSD was not affected with chronic treatment with haloperidol.…”
Section: Behaviour Models Of Chronic Antipsychotic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with schizophrenia, optimal treatment with antipsychotic drugs requires weeks to months of sustained drug therapy (Agid et al, 2003;Lieberman et al, 2008;Nestler and Hyman, 2010). It has been recently shown that chronic treatment with the atypical antipsychotics clozapine or risperidone, but not with the typical antipsychotic haloperidol, decreases the density of 5-HT 2A receptor in mouse frontal cortex (Gonzalez-Maeso et al, 2008;Kurita et al, 2012;Moreno et al, 2013b). Similar effects of chronic antipsychotic treatment have been reported in postmortem human brain of schizophrenic subjects.…”
Section: Discussionmentioning
confidence: 72%
“…For chronic treatment with typical and atypical antipsychotic drugs in mouse models, it has been demonstrated that chronic treatment with atypical antipsychotics markedly decreases the density of 5-HT 2A receptors in frontal cortex. 8284 Considering that the density of 5-HT 2A receptors is increased in post-mortem frontal cortex of antipsychotic-free schizophrenic subjects, and reduced to control levels in postmortem frontal cortex of antipsychotic-treated schizophrenic subjects, 84,85 these findings suggest that down-regulation of 5-HT 2A receptor density by chronic atypical antipsychotic treatment may be one of the molecular mechanisms involved in their therapeutic effects (see refs 86 and 87 for review articles discussing the level of expression of 5-HT 2A receptor in the schizophrenia brain). However, it was also demonstrated that this down-regulation of 5-HT 2A receptor density in mouse frontal cortex by chronic treatment with atypical antipsychotic drugs leads to down-regulation of the transcription of mGlu2 , an effect that was associated with repressive histone modifications at the promoter region of the mGlu2 gene in mouse and human frontal cortex.…”
Section: Role Of Epigenetic Mechanisms In Serotonin-dependent Signalingmentioning
confidence: 99%